The Effect Of Economic Value Added (Eva), Market Value Added (MVA), Refined Economic Value Added (REVA) On Stock Prices And Stock Returns In Manufacturing Companies Listed In Indonesia Stock Exchange - Mariyani, Dede; Hariyanti, Hariyanti; Novida, Diah Rachmawatie (Institut Manajemen Wiyata Indonesia, 2023)
The development of stock returns of manufacturing companies shows fluctuating movements from year to year. Return movements like this indicate that the condition of the manufacturing company is unstable so that it has an impact on the resulting stock returns. This uncertainty will certainly create its own concerns for investors who will invest in shares in manufacturing companies. With this, it is important for investors to analyze the company's condition first so that the investment made can provide returns. One aspect of the company that can be assessed by investors is the company's performance through financial statements. Helfert (2012: 98) grouped company performance measurements into three groups, namely (1) Earning Measures, (2) Cash Flow Measures, (3) Value Measures. Performance measurement based on value measures is economic value added (EVA), market value added (MVA), and refined economic value (REVA) This performance measurement holds the view that increasing value means also increasing long-term shareholder investment returns. Steward (2013: 115) states that value measures are considered to have capabilities that exceed Another performance measurement, because it takes into account all factors related to the creation (value) of the company that have an impact on the increasing prosperity of shareholders. The purpose of this study is to test EVA, MVA, and REVA against stock prices and stock returns. In this study using a research sample of 104 manufacturing companies taken through random sampling in the period 2014-2016. Data analysis and hypothesis testing in this study used the Partial Least Square Path Modeling (PLS-SEM) method. The results of this study show that EVA, MVA, and REVA have a significant positive relationship with stock price and stock return . By looking at the results of this study, it shows that performance appraisal using the EVA, MVA, and REVA methods has a strong influence on stock prices and stock returns . This shows that value-based valuation is important because every investment cannot escape the consequences of the incurring cost of capital as compensation for the funds used to finance the investment. The return on an investment will only mean that if the amount of return exceeds the cost of capital incurred to realize the investment, measurement certainly requires an accurate valuation method.